Effectiveness Of Structured Teaching Programme On Level Of Knowledge Regarding Osteoporosis Among Pre Menopausal Women (Journal of Pharmaceutical Negative Results, 2022)
Apre experimental research design was adopted to evaluate effectiveness of structured teaching programme on level of knowledge regarding osteoporosis among pre menopausal women .women were selected through convenient sampling technique. post test majority was achieved 60 (100%) of women were getting adequate knowledge that there was a significant difference (P<0.05) between pre and post score. The mean pre t score was 13.80 (+2.09) where as in pre test was 28.07(+0.09) respectively.